A Pedagogical Mystique?: Lessons of Incorporating Feminism Into Skills-Based Communication Courses - Daniela Molta; Regina Luttrell; Christopher McCollough (Central States Communication Association, 2022)
It is imperative that today's advertising, journalism, mass communication, and public relations students are prepared to engage in corporate activism and corporate social responsibility communications once in the workforce. This article explores the need for incorporating equity-based pedagogy, using feminism as one of many approaches, into skills-based communication courses. The researchers conducted 20 qualitative interviews with academics to discuss various approaches, examples, and learnings. The findings suggest that using a feminist framework to teach skills: (1) enhances the skill being taught, (2) allows students to communicate more effectively, (3) builds life skills, and (4) comes in many forms. The article concludes with consideration to areas for future research and contributes to the understanding of academics engaged in a feminist approach to teaching skills-based communication courses.